Desalination of duck egg white by biocoagulation to obtain peptide‐ferrous chelate as iron delivery system: Preparation, characterization, and Fe2+ release evaluation in vitro. Issue 10 (14th September 2021) - Shi, Qiang; Wei, Meijuan; Chen, Hongbing; Gao, Jinyan; Tong, Ping
Abstract : Abstract: The annual output of salted duck egg white (SDEW) is estimated to be over 1.5 million tons in China, most of which is discarded due to high salt content. This has led to serious waste and environmental impact. Therefore, we developed an eco‐friendly biocoagulation separation technology by combining chitosan and sodium alginate in order to produce a novel iron‐binding peptide (DPs‐Fe2+) from SDEW. The structure of DPs‐Fe2+ was characterized by ultraviolet‐visible spectroscopy, fluorescence spectroscopy, and Fourier transform infrared spectroscopy, followed by measuring DPs‐Fe2+ response in a simulated digestion/Caco‐2 cell model. Results showed that chitosan and sodium alginate complex could remove 91.21% of salt from SDEW, and the protein recovery rate reached 95.50%. Characterization results indicated that DPs bonded with Fe2+ to form a soluble chelate. Moreover, Caco‐2 cell monolayer model indicated that the transport rate of Fe2+ was as high as 10.02% at 0.1 mg/ml concentration of digested chelates. The results demonstrate the potential application of DPs as a novel carrier for enhancing iron absorption. This research contributes to the development of an effective industrial desalination method and highlights an opportunity for recycling an otherwise discarded processing byproduct. Practical Application: Salted duck egg whites (SDEW) are the primary byproduct of salted egg yolk production, most of which is discarded due to high salt content. Hence, efficient utilization of the high‐value proteins in SDEW is an urgent problem that must be resolved. Herein, we developed an effective industrial desalination method by combining chitosan and sodium alginate, which achieved excellent SDEW desalination and protein recovery. Furthermore, we produced a novel iron‐binding peptide (DPs‐Fe2+), which enhanced the transportation and absorption of Fe2+ in Caco‐2 cell model, suggesting its potential as an iron supplement.